2007
DOI: 10.2136/sssaj2006.0057
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Soil Nitrogen Tests for Corn Fertilizer Recommendations in the Humid Southeastern USA

Abstract: C urrently recommended N management in North Carolina and elsewhere in the humid southeastern USA is based on realistic yield expectations (RYE). In North Carolina, N recommendations based on RYE are made from a database of RYE by soil map unit or based on a grower's documented historic yields (the average of the best three yields during a 5-yr period; North Carolina Nutrient Management Workgroup, 2003). The recommended N rate is calculated using the RYE and a soil-and crop-dependent N application factor (18-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
35
1
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(45 citation statements)
references
References 16 publications
6
35
1
2
Order By: Relevance
“…Since its development, the Illinois soil N test has been evaluated by many researchers who have reported both successes in using the Illinois soil N test to differentiate N responsive from nonresponsive sites Mulvaney et al, 2006;Sharifi et al, 2007;Williams et al, 2007aWilliams et al, , 2007b and failures (Barker et al, 2006;Laboski et al, 2008;Osterhaus et al, 2008).…”
Section: Illinois Soil Nitrogen Testmentioning
confidence: 99%
“…Since its development, the Illinois soil N test has been evaluated by many researchers who have reported both successes in using the Illinois soil N test to differentiate N responsive from nonresponsive sites Mulvaney et al, 2006;Sharifi et al, 2007;Williams et al, 2007aWilliams et al, , 2007b and failures (Barker et al, 2006;Laboski et al, 2008;Osterhaus et al, 2008).…”
Section: Illinois Soil Nitrogen Testmentioning
confidence: 99%
“…Substantial research eff orts have focused on the utilization of the ISNT as a method to predict corn response and N fertilizer needs, but results have been mixed with limited success. Williams et al (2007aWilliams et al ( , 2007b successfully correlated and calibrated the ISNT for corn economic optimum N rates (EONR) in North Carolina and showed that the ISNT's predictive ability was enhanced when soils were categorized based on drainage classifi cation. A study by Ruff o et al (2006) identifi ed ISNT as the single most important parameter evaluated in conjunction with site-specifi c yield-response functions.…”
Section: Predicting Nitrogen Fertilizer Needs For Rice In Arkansas Usmentioning
confidence: 99%
“…Methods based on yield response curves cannot explain the spatial and temporal variation found in practice (i.e. curves often obtained from former field trials and other sites) (Williams et al, 2007). Methods based on soil testing involve the problem of searching for a reliable testing index.…”
Section: Introductionmentioning
confidence: 99%